Improved tibiofemoral contact restoration after transtibial reinsertion of the anterior root of the lateral meniscus compared to in situ repair: a biomechanical study - Espejo-Reina, Alejandro; Prado-Novoa, María; Espejo-Baena, Alejandro; Estébanez-Campos, María Belén; Pérez-de-la-Blanca-Cobos, Ana María (Springer, 2023)
Purpose: To compare biomechanical behaviour of the anterior root of the lateral meniscus (ARLM) after a transtibial repair (TTR) and after an in situ repair (ISR), discussing the reasons for the efficacy of the more advantageous technique. Methods: Eight cadaveric human knees were tested at flexion angles from 0° to 90° in four conditions of their ARLM: intact, detached, reinserted using TTR, and reinserted using ISR. Specimens were subjected to 1000 N of compression, and the contact area (CA), mean pressure (MP), and peak pressure (PP) on the tibial cartilage were computed. For the TTR, traction force on the sutures was registered. Results: ARLM detachment significantly altered contact biomechanics, mainly at shallow flexion. After ISR, differences compared to the healthy group persisted (extension, CA 22% smaller (p = 0.012); at 30°, CA 30% smaller (p = 0.012), MP 21%, and PP 32% higher (both p = 0.017); at 60°, CA 28% smaller (p = 0.012), MP 32%, and PP 49% higher (both p = 0.025). With TTR, alterations significantly decreased compared to the injured group, with no statistical differences from the intact ones observed, except for CA at extension (15% decrease, p = 0.012) and at 30° (12% decrease, p = 0.017). The suture tension after TTR, given as mean(SD), was 36.46(11.75)N, 44.32(11.71)N, 40.38(14.93)N, and 43.18(14.89)N for the four tested flexion angles. Conclusions: Alterations caused by ARLM detachment were partially restored with both ISR and TTR, with TTR showing better results on recovering CA, MP, and PP in the immediate postoperative period. The tensile force was far below the value reported to cause meniscal cut-out in porcine models.
Keywords: Biomecánica; Rodilla; Anterior meniscal root avulsion; Transtibial repair; In situ repair; Biomechanical testing